Coupled Multiple Sliding-Mode Control for Robust Trajectory Tracking of Hovercraft with External Disturbances - Jeong, Seongchan; Chwa, Dongkyoung (IEEE Transactions on Industrial Electronics, 2018)
This paper proposes a robust coupled multiple sliding-mode control (CMSMC) method for tracking control of underactuated hovercraft systems with nonholonomic constraints and external disturbances. First, a friction model for the hovercraft, one of the main disturbance factors, is proposed by considering viscosity, and its validity is demonstrated through experiments. Second, a disturbance model in the actual hovercraft system is estimated using a least-square-estimation-based disturbance observer. Third, pseudo forces and pseudo heading direction angle for tracking control and disturbance compensation are proposed considering the characteristics of underactuated hovercraft systems. Fourth, coupled multiple sliding surfaces (CMSSs) are newly introduced in terms of the tracking errors between the pseudo control variables and actual ones, and then, a CMSMC-based controller is proposed so that the CMSSs converge to zero within finite time in the case of zero disturbance estimation errors. In this way, three posture variables of the hovercraft converge to reference ones using only two control inputs. Finally, stability analysis and verification by simulations and experiments show that both the pseudo control tracking errors and posture tracking errors are ultimately bounded and asymptotically converge to zero when disturbance estimation errors become zero.
Keywords: Disturbance compensation; Disturbance observer; Multiple sliding mode control; Multiple sliding surfaces; Non holonomic constraint; Reference trajectories; Robust tracking control; Siding mode controls; Coupled multiple siding-mode control (CMSMC); disturbance compensation; disturbance observer; hovercraft; robust tracking control